A study on heuristic timetabling method for faculty course timetable problem - Lih, Bong Chia; Nah, Sze San; Noor Alamshah, Bolhassan (Institute of Electrical and Electronics Engineers Inc., 2015)
This paper studies university course timetabling problem in a case study related to faculty management system, which is concerned with assigning students/lecturers to classes and time-slots. In order to increase flexibility choices of timeslot for "repeaters", the problem has become more tight in scheduling. A two-stage heuristic approach is presented, where the initial stage groups the courses that are able to conduct simultaneously. The second stage then assigns the weekly timeslots for each group of courses, followed by venue for each course. Computational results are presented for the proposed solution using real data. It shows that the proposed solution is effective to handle the faculty course timetabling